Mastering the challenges of leading change : inspire the people and succeed where others fail - Dallas, H. James, 1958- (John Wiley & Sons, Inc., 2015)
Conquer the most daunting change initiative with the right people, tools, and strategies. James Dallas' Mastering the Challenges of Leading Change is an informative, insightful guide to effectively leading the transition through change. While most change management books present case studies about what happened at other companies, this book is based on the author's own experiences managing over 10 transformational and turnaround initiatives, 15 acquisition integrations, and 5 operations/quality shared services centers of excellence. By relating personal lessons learned, how they were subsequently applied, and how you can benefit from them, this book provides a unique first-hand perspective on successful agents of change. You'll learn the qualities and skills required to usher in the new paradigm, and how to break a large initiative into manageable chunks that are more likely to proceed as planned. By crafting your strategy based on proven methods, you're far and away more likely to meet or even exceed your change objectives. The majority of change initiatives fail because people mistakenly think that a change agent is the same as a project leader. They're not. This book shows you why, and how get the tools, strategies, and people you need at the helm of your initiative to come out the other side much stronger as an organization. Learn the critical skills required for effective change management Assess the difficulty and politics of a change initiative Choose the right people to help implement the change See past obstacles and lead effectively in a crisis Change is occurring within and across all industries, countries, and organizations. They begin with the best of intentions, but most fail to meet their objectives. Don't let your organization be one of the failures. Mastering the Challenges of Leading Change shows you how to plan, lead, and manage a successful transition.